EXPLORING TRANSMEDIA STORYTELLING TO FOSTER STUDENTS' TRANSLITERACY IN AN EFL CLASSROOM - Muhammad Amir Zikri, - (2019)
The research investigates the potential of Transmedia Storytelling to foster students' transliterate reading. The research was aimed to explore the potential of Transmedia Storytelling to foster students' transliterate reading. It was also conducted to identify the enabling and inhibiting factors for learning transliterate reading. Transmedia Storytelling in this research was the material that is being presented to the students during the teaching and learning session. Transliterate Reading, holds the meaning of the ability of the students in reading through multiple of media platforms that were being presented in the class. A case study was employed as a research design in this research. The data from this research were collected through two major instruments which were classroom observation and student's response sheets. The result from the data that had been obtained revealed that Transmedia Storytelling facilitate students' transliterate reading through multiple types of media namely: visuals, audios and interactive activities. Therefore, the use of Transmedia Storytelling to foster students' transliterate reading was evident as the media platforms helped the students' in reading the material that was being presented to them.